CBS Microdata - Slager, TJ (International Journal of Population Data Science, 2026)
CBS microdata is a valuable resource that provides researchers secure access to nearly all individual-level data available within Statistics Netherlands (CBS). The data is originated from administrative registers (e.g., Dutch Tax Authority, Personal records database (BRP)) and statistical surveys conducted by CBS. As such, CBS microdata includes information on individuals, households, businesses, and more, making it highly relevant for demographic, sociological and economic research. One of the key strengths of CBS microdata is its ability to link diverse datasets, enabling researchers to connect individuals to households, jobs to individuals, companies to jobs, and many other relationships. Furthermore, data can be linked across time, allowing for in-depth longitudinal studies. Researchers can also upload their own datasets, which can be pseudonymized and linked with CBS microdata to create even richer data analyses. CBS places a high priority on data security. Access to CBS microdata is strictly controlled and granted only to authorized institutions. Universities, scientific organizations, and public policy institutes in EEA countries can request authorization. All research is carried out within a secure CBS microdata environment, with privacy safeguards in place to ensure no individual-level data leaves this environment. Thanks to the vast amount of data, it’s detailed level, the ability to link datasets, and robust data security, CBS microdata provides valuable insights into complex societal trends and relationships and therefore plays a vital role in supporting scientific or statistical research. More information can be found here: https://www.cbs.nl/en-gb/our-services/customised-services-microdata/microdata-conducting-your-own-research.